(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Self-compacting concrete has emerged as a creative invention that is capable of solving the problem and making a remarkable advancement in the field of substantial innovation, which has led to the prior practise of substantial design free from vibration. Self-compacting concrete use today is focused on higher performance, better and more solid quality, and uniformity. Self compacting concrete (SCC) with GGBS and blended steel strands is being created in this research. The goal of this work is to create M30 SCC with GGBS cream steel fibers and compare its strength to normal concrete. The IS 10262 2009 standard is used to produce regular cement, whereas the alter Nan Su approach is used to produce SCC. In order to increase the volume of cement, the significant is replaced by 0, 10, 20, 30, and 40% of GGBS with the addition of stable steel strands at a 0.5% expansion. The compressive strength of SCC is determined using 3D squares of size 150x150x150mm, while the split tensile strength is determined using cylinder-shaped examples of size 150x300mm, and the flexural strength of SCC is determined using crystals of size 100x100x500mm.